DEVELOPMENT OF THE TELUK GELAM URBAN AREA, OGAN KOMERING ILIR REGENCY, SOUTH SUMATRA PROVINCE - Ahmad Fuad; Abdiyanto (Bulletin of Engineering Science, Technology and Industry, 2025)
This study aims to develop the Teluk Gelam Urban Area, Ogan Komering Ilir Regency, as a strategic collection and distribution center that serves the needs of the Teluk Gelam District community and its surroundings. The strategic location of the area, close to Kayu Agung City and located on the East Sumatra Cross-Island Road, has great potential for sustainable regional development. This study uses a mixed method with a quantitative and qualitative approach, supported by secondary data and field observations. The analysis includes spatial structure, land capability, accessibility, and environmental carrying capacity and capacity. The results of the study indicate that there are three levels of service center hierarchy, namely the Area Service Center (PPK) in Mulya Guna, Sub Area Service Center (SPPK) in Menang Raya, Seriguna, and Talang Pangeran, and Local Service Center (PPL) in other villages. Areas with high accessibility are directed for further development, while areas with low land capability are directed for conservation. This study provides a strong planning framework for sustainable and equitable regional development in the Teluk Gelam Urban Area.